2018
DOI: 10.3126/bjhs.v3i2.20945
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Intra Operative Blood Sugar Level in Spinal Anesthesia and General Anesthesia in Patients undergoing Elective Surgery

Abstract: Introduction: The aim of the study was to carry out the comparative study of variations in blood glucose levels intra operatively in patients undergoing surgical procedures in Spinal Anesthesia and General Anesthesia by capillary blood glucose level.Objective: To compare intra operative blood glucose level in Spinal and General Anesthesia.Methodology: Sixty non diabetic patients (30 in each group) aged between 20 – 60 years belonging to ASA I and ASA II status were enrolled for this prospective comparative stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In contrast to our study, a study conducted by Bajracharya et al . 19 found in patients who underwent elective surgery under SA, each measurement of intraoperative blood glucose levels at different time intervals was slightly decreased from baseline value without significant difference ( P >0.05). Another study also found that there is no significant change in blood glucose levels from a baseline value throughout a procedure in both diabetic mellitus and Non-diabetic mellitus patients undergoing hip surgery under SA 32 .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In contrast to our study, a study conducted by Bajracharya et al . 19 found in patients who underwent elective surgery under SA, each measurement of intraoperative blood glucose levels at different time intervals was slightly decreased from baseline value without significant difference ( P >0.05). Another study also found that there is no significant change in blood glucose levels from a baseline value throughout a procedure in both diabetic mellitus and Non-diabetic mellitus patients undergoing hip surgery under SA 32 .…”
Section: Discussionmentioning
confidence: 75%
“…The sample size was calculated using a comparison of two means in the formula for continuous outcomes with equal sample size; based on a previous study done in Nepal 19 which showed, the mean and standard deviation of the mean blood glucose level in the GA group is (86.32±12.3 mg/dL) and in SA group is (95.36±14.15 mg/dL), with µ 1= 86.32, σ 1= 12.3 and µ 2= 95.36, σ 2= 14.1, and with an alpha error of 0.05 at a power of 80%.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that heat tolerance is impaired in obese patients. 24 Perioperative hypothermia in patients with DAN may be associated with the disability of the body to increase heat production by metabolic factors or decrease blood flow to the skin via vasoconstriction. 22 Autonomic neuropathy may slow down the onset of feedback thermoregulatory constriction of blood vessels and may diminish its effectiveness once activated.…”
Section: Temperaturementioning
confidence: 99%